The Role of Fall Risk-Increasing Drugs in Prevalence of Fall and its Associated Factors - Fairul Ezwan Fahrurazi; Khairul Naim bin Ghazali; Nur Syazwani binti Shahrom (Journal of Pharmacy)
Introduction: The World Health Organization defines a fall as "an event where a person comes to rest inadvertently on the ground or another lower level”. Among numerous risk factors, medication use stands out as one of the most highly modifiable risk factors for falls in adults. Medications associated with an increased fall risk have been termed Fall Risk–Increasing Drugs (FRIDs). This study aimed to determine the prevalence of falls among patients at Hospital Baling and its associated factors. Methods: A cross-sectional study was conducted by examining patients' history of falls and medication records for those admitted to the ward from 1st January to 30th June 2023. Systematic random sampling was used, and multiple logistic regression was performed to determine the risk factors for falls. Types of FRIDs were extracted from the Comprehensive Falls Risk Assessment Instrument (FRAI) and scored based on prescribed medications. Results: A total of 200 medical records were examined. The prevalence of falls among patients was 10.5% whereby the mean FRAI score was 2.32. Patients using diuretics were 81% less likely to experience falls (adjusted OR = 0.19, 95% CI [0.04, 0.94], p = 0.038), while each additional comorbidity increased the odds of falling by 2.2 times (adjusted OR = 2.20, 95% CI [1.38, 3.51], p = 0.001). Conclusion: FRIDs, except for diuretics, did not show any significant association with falls. However, thorough medication review by pharmacists remains essential, despite FRIDs showing little to no difference in increasing risk of falls.